2008
DOI: 10.1037/a0012666
|View full text |Cite
|
Sign up to set email alerts
|

The role of control motivation in mortality salience effects on ingroup support and defense.

Abstract: Terror management research has shown that mortality salience (MS) leads to increased support and defense of cultural ingroups and their norms (i.e., worldview defense, WD). The authors investigated whether these effects can be understood as efforts to restore a generalized sense of control by strengthening one's social ingroup. In Studies 1-3, the authors found that WD was only increased following pure death salience, compared with both dental pain salience and salience of self-determined death. As both the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
272
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(296 citation statements)
references
References 100 publications
14
272
1
9
Order By: Relevance
“…In fact, Stollberg et al ( 2015 ) found that, when reminded of lacking personal control, people were more prone to identify with agentic (vs. non-agentic) groups. In addition to mere identifi cation, people have been shown to cope with threatened personal control by engaging in collective behaviour, indicated by increased in-group bias (Fritsche, Jonas, & Fankhanel, 2008 ;Greenaway, Louis, Hornsey, & Jones, 2014 ), conformity with in-group norms (Stollberg, Fritsche, & Jonas, submitted ), and pursuit of in-group goals . The latter effects of threatened personal control have been shown to be most pronounced when in addition to personal control threat, in-group agency was also at stake or when in-group identifi cation was high submitted ).…”
Section: Behavioural Motives Of Identitymentioning
confidence: 98%
“…In fact, Stollberg et al ( 2015 ) found that, when reminded of lacking personal control, people were more prone to identify with agentic (vs. non-agentic) groups. In addition to mere identifi cation, people have been shown to cope with threatened personal control by engaging in collective behaviour, indicated by increased in-group bias (Fritsche, Jonas, & Fankhanel, 2008 ;Greenaway, Louis, Hornsey, & Jones, 2014 ), conformity with in-group norms (Stollberg, Fritsche, & Jonas, submitted ), and pursuit of in-group goals . The latter effects of threatened personal control have been shown to be most pronounced when in addition to personal control threat, in-group agency was also at stake or when in-group identifi cation was high submitted ).…”
Section: Behavioural Motives Of Identitymentioning
confidence: 98%
“…For instance, researchers have used an autobiographical memory manipulation, by asking participants to recall and describe specific life episodes where they were lacking control (Kay, Gaucher, Napier, Callan, & Laurin, 2008;Rutjens, van der Pligt, & van Harreveld, 2010); participants have been shown pictures related to a loss of control (de Arcos, Verdejo-Garcia, Peralta-Ramirez, Sanchez-Barrera, & Perez-Garcia, 2005); participants have been instructed to complete unsolvable tasks (Reed, Frasquillo, Colkin, Liemann, & Colbert, 2001); or participants performed a task in which they did not have control over actions they were asked to perform (Maier & Seligman, 1976). By using these manipulations it has been found that control threat results in a stronger endorsement of spiritual beliefs (Kay et al, 2009), a stronger belief in paranormal abilities (Greenaway, Louis, & Hornsey, 2013), an enhanced tendency to detect illusory patterns in noise (Whitson & Galinsky, 2008), a stronger attachment towards in-groups (Agroskin & Jonas, 2014;Fritsche et al, 2013;Fritsche, Jonas, & Fankhanel, 2008), a stronger preference for governmental control (Kay et al, 2008), more belief in science (Rutjens et al, 2010), and more prejudice toward outgroup members (Greenaway, Louis, Hornsey, & Jones, 2014). Thus, the empirical evidence for the notion that lack of control triggers compensatory strategies for restoring subjective feelings of control and predictability is quite impressive (for recent review, see : Landau et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way that people turn to interpersonal others and social groups to help them cope with various psychological needs and problems (e.g., Fritsche, Jonas, & Fankhänel, 2008;Harkins, Latané, & Williams, 1980;Latané, Williams, & Harkins, 1979;Tajfel & Turner, 1986), so too do they turn to their political and institutional systems. As such, to the extent that an important issue is presented to people in a way that makes it appear especially complex, rather than motivating increased individual effort at addressing that issue, it may elicit increased dependence on the government.…”
mentioning
confidence: 99%